Achieving high convective volume in hemodiafiltration: Lessons learned after successful implementation in the HDFit trial. Issue 1 (15th October 2020) - Guedes, Murilo; Dambiski, Ana Claudia; Canhada, Sinaia; Barra, Ana Beatriz L.; Poli‐de‐Figueiredo, Carlos Eduardo; Cuvello Neto, Américo Lourenço; Canziani, Maria Eugênia F.; Strogoff‐de‐Matos, Jorge Paulo; Raimann, Jochen G.; Larkin, John; Canaud, Bernard; Pecoits‐Filho, Roberto; et al.
Abstract: Background and objectives: High‐volume online hemodiafiltration (OL‐HDF) associates with improved outcomes compared to hemodialysis (HD), provided adequate dosing is achieved as estimated from convective volume (CV). Achievement of high CV and its impact on biochemical indicators following a standardized protocol converting HD patients to OL‐HDF has not been systematically reported. We assessed the success of implementation of OL‐HDF in clinics naïve to the modality. Design, setting, participants, and measurements: We analyzed the results of the implementation of postdilution OL‐HDF in patients randomized to the HDF arm of a clinical trial (impact of hemoDiaFIlTration on physical activity and self‐reported outcomes: a randomized controlled trial (HDFit) trial [ClinicalTrials.gov :NCT02787161]). The day before randomization of the first patient to OL‐HDF at each clinic staff started a 3‐day in‐person training module on operation of Fresenius 5008 CorDiax machine in HDF mode. Patients were converted from high‐flux HD to OL‐HDF under oversight of trainers. OL‐HDF was performed over a 6‐months follow‐up with a CV target of 22 L/treatment. We characterized median achieved CV >22 L/treatment record and analyzed the impact of HDF on biochemical variables. Results: Ninety‐seven patients (mean age 53 ± 16 years, 29% with diabetes, and 11% had a catheter) from 13 clinics randomized to the OL‐HDF arm of the trial were converted from HD to HDF. Median CV > 22 L/treatment was achieved in 99% (94/95) of OL‐HDF patients throughout follow‐up. Monthly mean CV ranged from 27.1 L to 27.5 L. OL‐HDF provided an increased single pool Kt/V at 3‐months (0.2 [95% CI: 0.1–0.3]) and 6‐months (0.2 [95% CI: 0.1–0.4]) compared to baseline, and reduced phosphate at 3‐months (−0.4 mg/dL [95% CI: −0.8 to −0.12]) of follow‐up. Conclusions: High‐volume online hemodiafiltration was successfully implemented with 99% of patients achieving protocol defined CV target. Monthly mean CV was consistently >22 L/treatment during follow‐up. Kt/V increased, and phosphate decreased with OL‐HDF. Findings resulting from a short training period in several dialysis facilities appear to suggest HDF is an easily implementable technique.